Odpowiedzi

2009-11-15T12:14:07+01:00
1). -16-(+10)-(-24)= -16 -10 + 24 = - 26 + 24 = -2
2). -(-19)-(+24)-(-15)= 19 - 24 + 15 = -5 + 15 = 10
3). -(-21)+(-31)-15= 21 - 31 - 15 = -10 - 15 = -25
4). 6+(-2)+(-3)-(-4)= 6 - 2 - 3 + 4 = 4 - 3 + 4 = 1 + 4 = 5
5). -21+(-3)-(-6)-(+5)= -21 - 3 + 6 - 5 = -24 + 6 - 5 = - 18 - 5 = -23

;)
2009-11-15T12:15:46+01:00
1. -16-(+10)-(-24)=-6-(-24)=-18
2). -(-19)-(+24)-(-15)=-5-(-15)=10
3). -(-21)+(-31)-15=-10-15=-25
4). 6+(-2)+(-3)-(-4)=5
5). -21+(-3)-(-6)-(+5)= 23
1 1 1
  • smq
  • Początkujący
2009-11-15T12:16:35+01:00
1). -16-(+10)-(-24)= -16-10+24=-2
2). -(-19)-(+24)-(-15)=19-24+15=10
3). -(-21)+(-31)-15=21-31-15=-25
4). 6+(-2)+(-3)-(-4)=6-2-3+4=5
5). -21+(-3)-(-6)-(+5)=-21-3+6-5=-23
pzdr ;)